A Simple Method to Evaluate Whether Pancreas Texture Can Be Used to Predict Pancreatic Fistula Risk After Pancreatoduodenectomy - TÜNEY, DAVUT; DULUNDU, ENDER; UĞURLU, MUSTAFA ÜMİT; YEGEN, ŞEVKET CUMHUR (SPRINGER, 2015)
Soft pancreas is one of the most important risk factor for postoperative pancreatic fistula after pancreatoduodenectomy. The aim of this study is to investigate whether pancreatic attenuation index utilized to assess the pancreatic texture with computed tomography can be used to predict the risk of developing a clinically relevant postoperative pancreatic fistula after pancreatoduodenectomy. We reviewed 76 consecutive patients undergoing pancreatoduodenectomy between 2012 and 2014. The pancreatic attenuation index is found by dividing the pancreas density by the spleen density achieved with non-enhanced computed tomography. The independent predictors of clinically relevant postoperative pancreatic fistula were investigated. Clinically relevant postoperative pancreatic fistula occurred in 13 patients (17.1 %). The group of patients with postoperative pancreatic fistula is compared with the group of patients without postoperative pancreatic fistula in terms of age, gender, body mass index, the American Society of Anesthesiologists (ASA) score, smoking, alcohol consumption, medical comorbidities, preoperative biliary drainage, type of anastomosis, and pancreatic duct size and pancreatic attenuation index. Univariate analyses have shown a significant difference in relation to chronic obstructive pulmonary disease and pancreatic attenuation index. The multivariate analyses showed that only pancreatic attenuation index was associated with a high postoperative pancreatic fistula rate (P = 0.012). A preoperative non-contrast computed tomography scan evaluating pancreatic attenuation index could help to predict the occurrence of clinically significant postoperative pancreatic fistula after pancreatoduodenectomy.
Keywords: Pancreatoduodenectomy; Computed tomography; Pancreaticojejunostomy; Pancreatic fistula; CONSECUTIVE PANCREATICODUODENECTOMIES; ANASTOMOTIC FAILURE; COMPUTED-TOMOGRAPHY; FATTY PANCREAS; CT; PANCREATICOGASTROSTOMY; MANAGEMENT; FIBROSIS; LEAKAGE; MASS